Rapid-onset hypernatremia induced by central diabetes insipidus leading to osmotic demyelination syndrome: a case report - Zhang, Yifan; Chen, Ruijun; Kong, Xiangxu; Yan, Yuexin; Su, Shengyuan (Frontiers in Medicine, 2025)
This case study describes a middle-aged male patient who developed persistent hypernatremia due to central diabetes insipidus (CDI), presenting with polyuria (up to 8.5 L/24 h), polydipsia, and hypotonic urine (urine specific gravity < 1.005). A positive response to the desmopressin test confirmed the diagnosis of CDI. The excessive loss of body water led to a peak serum sodium level of 195 mmol/L, resulting in Osmotic demyelination syndrome (ODS), clinically manifesting as sluggish responses and symmetrical limb paralysis. The patient was treated with hypotonic fluid replacement combined with desmopressin while ensuring a controlled reduction in serum sodium levels (≤10 mmol/L within 24 h). As a result, as serum sodium and urine output gradually normalized, the patient’s consciousness and limb strength progressively recovered. This case highlights the risk of ODS in patients with severe hypernatremia caused by CDI. A slow and controlled correction of serum sodium levels is crucial in preventing cerebral edema, and early rehabilitation plays a vital role in improving neurological outcomes.